2022
DOI: 10.1007/s10067-022-06348-z
|View full text |Cite|
|
Sign up to set email alerts
|

Immunogenicity and safety of the mRNA-based BNT162b2 vaccine in systemic autoimmune rheumatic diseases patients

Abstract: Background The COVID-19 outbreak has led to the rapid development and administration of the COVID-19 vaccines worldwide. Data about the immunogenicity and adverse effects of the vaccine on patients with systemic autoimmune rheumatic diseases (SARDs) is emerging. Aim To evaluate Pfizer/BioNTech (BNT162b2) mRNA-based vaccine second-dose immunogenicity and safety, and the relation between them, in patients with SARDs. Methods A total of one hundred forty tow adults who received two doses of the BNT162b2 vaccine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…We found that although the CFR decreases in the general population with increasing vaccination coverage, this effect is not observed in patients treated with CD20-targeting drugs or patients treated with glucocorticoids. This is in line with studies showing impaired humoral and cellular vaccination responses in patients under anti-CD20 treatment (Moor et al, 2021;Pri-Paz Basson et al, 2022;Wu et al, 2022) and studies showing that glucocorticoids impair the immunogenicity of the COVID-19 vaccine (Bugatti et al, 2021;Pri-Paz Basson et al, 2022). In contrast, in accordance with previous studies that found that the respective treatments do not significantly impair COVID-19 vaccination efficacy, we observed a decrease in CFRs for patients under anti-TNFα (Dimopoulou et al, 2022;Pri-Paz Basson et al, 2022;Venerito et al, 2022), JAK inhibitor (Winthrop et al, 2016;Mortezavi et al, 2021;Pri-Paz Basson et al, 2022), or thalidomide analog (Jenner et al, 2021) treatment.…”
Section: Discussionsupporting
confidence: 88%
“…We found that although the CFR decreases in the general population with increasing vaccination coverage, this effect is not observed in patients treated with CD20-targeting drugs or patients treated with glucocorticoids. This is in line with studies showing impaired humoral and cellular vaccination responses in patients under anti-CD20 treatment (Moor et al, 2021;Pri-Paz Basson et al, 2022;Wu et al, 2022) and studies showing that glucocorticoids impair the immunogenicity of the COVID-19 vaccine (Bugatti et al, 2021;Pri-Paz Basson et al, 2022). In contrast, in accordance with previous studies that found that the respective treatments do not significantly impair COVID-19 vaccination efficacy, we observed a decrease in CFRs for patients under anti-TNFα (Dimopoulou et al, 2022;Pri-Paz Basson et al, 2022;Venerito et al, 2022), JAK inhibitor (Winthrop et al, 2016;Mortezavi et al, 2021;Pri-Paz Basson et al, 2022), or thalidomide analog (Jenner et al, 2021) treatment.…”
Section: Discussionsupporting
confidence: 88%
“…Literature evidence reported an impaired immune proficiency, especially in the humoral arm, in the presence of autoimmune diseases under treatment [ 57 , 58 , 59 ]. Our analysis included a low number of individuals characterized by these clinical conditions; thus, we might not reach final conclusions in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…More studies focusing on the effect of steroids on regulatory cytokine expression and T-cells in the context of mRNA vaccines might contribute to a better understanding of the role of steroids in inhibiting the cellular response to mRNA vaccine. Further, studies show that anti-B cell therapy and glucocorticoid treatment were found to reduce the humoral response to two doses of the BNT162b2 vaccine 4 , 22 . However, the third dose of the vaccine was shown to increase the antibody titers also in immunosuppressed patients 23 , 24 .…”
Section: Discussionmentioning
confidence: 99%